Evolving epidemiology, clinical features, and genotyping of dengue outbreaks in Bangladesh, 2000–2024: a systematic review - Sharif, Nadim; Opu, Rubayet Rayhan; Saha, Tama; Masud, Abdullah Ibna; Naim, Jannatin; Alsharif, Khalaf F.; Alzahrani, Khalid J.; Alvarado, Eduardo Silva; Noya, Irene Delgado; De la Torre Díez, Isabel; Dey, Shuvra Kanti (Frontiers in Microbiology, 2024)
The 2023-dengue outbreak has already proven that dengue is not only an endemic disease but also an emerging health threat in Bangladesh. Integrated studies on epidemiology, clinical characteristics, seasonality and genotype of dengue are limited. This study was performed to determine the recent trends on the molecular epidemiology, clinical features, and seasonality of dengue outbreaks.We analyzed 41 original studies for collecting different data. Epidemiological data from 41 articles, clinical symptoms from 30, genotypic diversity from 11 articles were extracted. The standards of the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA)Statement and Cochrane Collaboration were followed for conducting the study.Results: A total of 565438 cases and 2587 fatalities of dengue virus have been documented from January 2000 to March 2024 in Bangladesh. About 91% (515262 of 565438) of the cases were documented during 2019-2024. Majority of the cases (60%) in 2019 and 2023 outbreaks were reported from regions previously documented as non-endemic. Frequency of fatalities were higher in female (70%). Majority of the studies (95-100%) used NS1Ag test followed by IgG or IgM and RT-PCR tests. The southern (Khulna, 10.8% and Barishal, 11.8%) and southeastern regions (Chattogram, 13.8%) became new hotspots of dengue transmission in Bangladesh. Serotyping was conducted on 92.4% (1456 of 1575) of the isolates during 2012-2023. Among the four serotypes, DENV3 (57%) was the most prevalent followed by DENV2 (30%), DENV1 (11%) and DENV4 (<1%), respectively. Genotype DENV3-I (43 of 59) was the most prevalent followed by DENV3-II (8 of 59). The highest frequency of dengue virus case was found in August (26.3%), followed by September (22.5%), October (20.2%), and November (13.08%), respectively. Fever (90.51%, 95% CI 85%-100%) was the most prevalent symptom followed by headache (57.98%, 95% CI 12%-100%), vomiting (51.16%, 95% CI 23%-91%), abdominal pain (34.12%, 95% CI 12%-85%), and myalgia (25.53%, 95% CI 13%-85%), respectively.This study will add integrated knowledge on molecular epidemiology, clinical features, seasonality and transmission of dengue virus and identify research gap for future works.